Right to collective action in cross-border employment contexts: a fundamental social right not yet covered by EU private international law - Peraro, Cinzia (UNIO – EU Law Journal, 2016)
The purpose of this article is to describe the right to collective action in crossborder employment contexts, recognised as a fundamental social right at the national and European levels. On the one hand, some national Constitutional Courts, such as the Portuguese and Italian ones, have dealt with social rights and the economic crisis, and have clearly stressed the prevalence of constitutional social rights over austerity measures. On the other hand, Council of Europe documents and European Union law recognise social rights, but they do not offer a proper means of protection. The European Court of Justice case-law shows a complex interrelation between social rights and economic freedoms. The main issue concerns the existing EU private international law on collective action, which has led to an inconsistent system. A new European collective action framework could be a possible solution to effectively guarantee fundamental social rights.